2021
DOI: 10.1007/s10668-021-01948-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the environmental impacts of paracetamol dosage forms using life cycle assessment

Abstract: A medicine can be administered in varied dosage forms which are having different environmental impacts. Two dosage forms of paracetamol (tablet and syrup) have the same function but are prepared and packaged differently, meaning that the environmental impacts arising out of their production will be of different magnitude. This study utilizes the life cycle assessment technique to find and compare the environmental impacts of two dosage forms of the paracetamol. Life cycle assessment software 'GaBi' v 8.0 has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…A 2021 review of surgical equipment concluded that the provision and use of singleuse surgical equipment tends to have a larger environmental impact across a broad range of parameters, including GWP, acidification, eutroph ication, ozone depletion, and smog formation, compared with equivalent reusables. 21 Environmental impacts have been evaluated for a range of pharmaceutical agents, including anaesthetics, [117][118][119][120] anal gesics, 26,117,[121][122][123][124][125] antibiotics, 26,[126][127][128] antiemetics, 117 antide pres sants, 129 bronchodilators, [130][131][132] inhaled corticosteroids, 130,131 medical oxygen, 133 monoclonal antibodies, 134 muscle relax ants and reversal agents, 117 phosphodiesterase inhibitors, 135 sedatives, 117 sympathomimetics, 117 vitamins, 136 and vac cines. 137,138 Impacts were most commonly reported by kilograms of active pharmaceutical ingredient, with wide ranging estimates (2•3 kg CO 2 e for naproxen 26 to 280 000 kg CO 2 e for nivolumab; 134 appendix pp 7-8).…”
Section: Environmental Impacts Of Health-care Productsmentioning
confidence: 99%
“…A 2021 review of surgical equipment concluded that the provision and use of singleuse surgical equipment tends to have a larger environmental impact across a broad range of parameters, including GWP, acidification, eutroph ication, ozone depletion, and smog formation, compared with equivalent reusables. 21 Environmental impacts have been evaluated for a range of pharmaceutical agents, including anaesthetics, [117][118][119][120] anal gesics, 26,117,[121][122][123][124][125] antibiotics, 26,[126][127][128] antiemetics, 117 antide pres sants, 129 bronchodilators, [130][131][132] inhaled corticosteroids, 130,131 medical oxygen, 133 monoclonal antibodies, 134 muscle relax ants and reversal agents, 117 phosphodiesterase inhibitors, 135 sedatives, 117 sympathomimetics, 117 vitamins, 136 and vac cines. 137,138 Impacts were most commonly reported by kilograms of active pharmaceutical ingredient, with wide ranging estimates (2•3 kg CO 2 e for naproxen 26 to 280 000 kg CO 2 e for nivolumab; 134 appendix pp 7-8).…”
Section: Environmental Impacts Of Health-care Productsmentioning
confidence: 99%
“…In the management area, studies have examined the circular economy (di Vaio et al, 2023 ; Mirzaei & Shokouhyar, 2022 ; Rasool et al, 2022 ), life cycle analysis (Hayek et al, 2021 ; Khaddour, 2022 ; Sharma et al, 2022 ) while only one study investigated the impact of sustainability disclosure on corporate performance (Ellili & Nobanee, 2022 ). Through a bibliometric analysis, this study was not only able to identify the most frequent sustainability topics published in Environment, Development and Sustainability , but also detect various gaps in the literature and propose paths for future research.…”
Section: Introductionmentioning
confidence: 99%